(untitled) (Modern information system and technologies, 2018)
The article provides a detailed analysis of the currently existing authentication systems: password, hardware, biometric. The classification of access systems for information is carried out. The general advantages and disadvantages of systems are considered. The basic characteristics of authentication systems are presented. The general model of work of systems of authentication of users of information-computer system is provided. Keywords: Protection of information, authentication system, password, hardware, biometric authentication.